Therapeutic Potential of Polyphenol and Nanoparticles Mediated Delivery in Periodontal Inflammation: A Review of Current Trends and Future Perspectives - Putri Ayu Jayusman; Nurrul Shaqinah Nasruddin; Nurul Inaas Mahamad Apandi; Norliwati Ibrahim; Siti Balkis Budin (Frontiers Media S.A., 2022)
Periodontitis is an oral inflammatory process involving the periodontium, which is mainly caused by the invasion of periodontopathogenic microorganisms that results in gingival connective tissue and alveolar bone destruction. Metabolic products of the oral pathogens and the associated host immune and inflammatory responses triggered are responsible for the local tissue destruction. Numerous studies in the past decades have demonstrated that natural polyphenols are capable of modulating the host inflammatory responses by targeting multiple inflammatory components. The proposed mechanism by which polyphenolic compounds exert their great potential is by regulating the immune cell, proinflammatory cytokines synthesis and gene expression. However, due to its low absorption and bioavailability, the beneficial effects of these substances are very limited and it hampers their use as a therapeutic agent. To address these limitations, targeted delivery systems by nanoencapsulation techniques have been explored in recent years. Nanoencapsulation of polyphenolic compounds with different carriers is an efficient and promising approach to boost their bioavailability, increase the efficiency and reduce the degradability of natural polyphenols. In this review, we focus on the effects of different polyphenolic substances in periodontal inflammation and to explore the pharmaceutical significance of polyphenol-loaded nanoparticles in controlling periodontitis, which may be useful for further enhancement of their efficacy as therapeutic agents for periodontal disease.